The impact of age on number and distribution of proliferating cells in subgranular zone in adult mouse brain. (June 2019) - Smith, Karen; Semënov, Mikhail V.
Abstract: The mouse brain retains an ability to produce hippocampal granule neurons during the mouse's entire lifespan. The neurons are produced in the subgranular zone (SGZ) located on the inner surface of the granule cell layer in the dentate gyrus (DG). In our study, we used a point cloud approach to characterize how the production and distribution of neural precursors for new hippocampal neurons change in the mouse brain relative to age. We found that the production of neural precursors decreases 64 fold from the age of 30 days to the age of 2.5 years. Within the SGZ the decline of cell proliferation continues during entire mouse life. We reconstructed the distribution of proliferating cells along the longitudinal axis of the SGZ and found that the highest number of proliferating cells are located approximately 0.75 mm from the dorsomedial end of the SGZ that corresponds to the most dorsal part of the DG in the mouse brain. The distribution of proliferating cells in the SGZ showed no apparent aggregations, periodicity or any other readily identifiable spatial characteristics. Proliferating cells in the SGZ tended to be located separately from other proliferating cells. About two thirds of them have no closely located other proliferating cells, and the remaining third is located in small clusters comprised of 2 or 3 proliferating cells. Based on our measurements, we calculated that from the age of 30 days to the age of 2.5 years 1.5 million neural precursors are produced in the SGZ.